Androgen receptor, a possible anti-infective therapy target and a potent immune respondent in SARS-CoV-2 spike binding: a computational approach. Issue 3 (4th March 2023) - Ahmad, Ashfaq; Makhmutova, Zhandaulet; Cao, Wenwen; Majaz, Sidra; Amin, Amr; Xie, Yingqiu
ABSTRACT: Background: Although androgen in gender disparity of COVID-19 has been implied, no direct link has been provided. Research design and methods: Here, we applied AlphaFold multimer, network and single cells database analyses to highlight specificity of Androgen receptor (AR) against spike receptor binding protein (RBD) of SARS-CoV-2. Results: LXXL motifs in spike RBD are essential for AR binding. RBD LXXA mutation complex with the AR depicting slightly reduced binding energy, as LXXLL motif usually mediates nuclear receptor binding to coregulators. Moreover, AR preferred to bind a LYRL motif in specificity and interaction interface, and showed reduced affinity against Omicron compared to other variants (alpha, beta, gamma, and delta). Importantly, RBD LYRL motif is a conserved antigenic epitope (9 residues) for T-cell response. Network analysis of AR-related genes against COVID-19 database showed T-cell signaling regulation, and CD8+ T-cell spatial location in AR+ single cells, which is consistent with the AR binding motif LYRL in epitope function. Conclusions: We provided the potent mechanisms of AR binding to RBD linking to immune response and vaccination shift. AR could be an anti-infective therapy target for anti-Omicron new lineages.